Penyisihan Fosfat dan Amonium Pada Air Limbah Menggunakan Presipitasi Struvite Dengan Penambahan Bittern - Adhi Setiawan; Falenia Firdatul Jannah; Tarikh Azis Ramadani; Tanti Utami Dewi (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2022)
The fertilizer industry generally produces wastewater with relatively high ammonium and phosphate content, so processing is necessary so as not to cause eutrophication effects that harm the environment. Struvite precipitation with bittern media was an alternative method to remove struvite content in wastewater. This study aimed to analyze the effect of pH and molar ratio [Mg2+] : [NH4+] : [PO43-] on the struvite precipitation process in reducing the ammonium and phosphate content in the artificial wastewater of the fertilizer industry and to characterize the struvite obtained from the precipitation process. The precipitation process was conducted in batches with various pH and molar ratios [Mg2+]: [NH4+]: [PO43-]. The variation of pH used is 8−10. The molar ratios used are 1.5 : 1.0 : 1.0 and 3.0 : 1.0 : 1.0. Struvite characterization was conducted using SEM-EDX and XRD methods. The results showed that pH and molar ratio had an effect on the efficiency of removal ammonium and phosphate using struvite precipitation. The best pH value and molar ratio that can be used to remove content of ammonium and phosphate is at pH 9 with a molar ratio of [Mg2+] : [NH4+] : [PO43-] 3.0 : 1.0 : 1.0 which results in the removal efficiency of 86.50% and 99.96% respectively. The morphology of struvite obtained from precipitation is irregular rod-shaped with an average size of 28.53 μm. XRD results have detected peaks indicating the struvite phase.